PERANCANGAN PERKERASAN JALAN KOMPOSIT PADA RUAS JALAN KANITI DESA PENFUI TIMUR KABUPATEN KUPANG - Lourdes, Atrianus; Bela, Krisantos Ria; Pedo, Krisantus Satrio Wibowo (Program Studi Teknik Sipil Universitas Katolik Widya Mandira, 2023)
The condition of road infrastructure in East Penfui Village is inadequate on several road segments because road improvements are not commensurate with village growth. One of the village infrastructure improvement plans is improvements to the Kaniti Road section (Kaniti Bridge). Composite pavement planning on this section needs to be done as an alternative to selecting the right type of pavement. This research method uses a calculation method based on the rigid pavement layer thickness planning guidelines Pd-T-14-2003 and calculates flexible pavement layer thickness using component analysis methods. The design results are Jointed Reinforced Concrete Pavement with a design age of 20 years without concrete shoulders, a concrete slab thickness of 22 cm, a slab width of 5.5 m, a slab connection length of 5 m, shrinkage joints, and spokes and concrete transverse and longitudinal reinforcement. The plate thickness is 22 cm and meets the requirements of the fatigue and erosion analysis results. The results of designing the thickness of the composite pavement layer with a design life of 20 years consist of subgrade, sub-base in the form of aggregate A 10 cm thick, LMC (Lean Mix-Concrete) 15 cm thick, a surface layer in the form of a concrete slab 22 cm thick, and HRS (Hot Rolled Sheet) asphlalt is 5 cm thick..